Reshaping Today’s Education with Social Media - Fathul Qorib; Sitti Utami Rezkiawaty Kamil; Jumrana; La Tarifu (Jurnal Riset Public Relations, 2022)
Abstract. The government's move to suppress the spread of the covid-19 virus in Indonesia by limiting the meeting of a number of people has an impact on many lines of life including higher education institutions. Starting from 2020, the learning system undergoes the most fundamental change in the history of the transformation of the Education system. Through government program policies, learning that was initially held face-to-face then replaced with virtual meetings, the transformation of learning media is also massive, where there is a discussion of online learning media that support the implementation of virtual lectures becomes the main prerequisite. The development of communication technology plays an important role to be an option in an effort to provide learning media that can be utilized. Social media that appeared to support the learning management system. Using social media in order to trigger the quality of student learning by utilizing all the ease of communicating and sharing information owned by the media for the education or learning process becomes more effective and efficient and accelerates information as a whole. The method of the research is Mixed method research, were to combine the quantitative and qualitative methods used in this study with the aim of identifying students' digital literacy competencies related to learning media by filling out questionnaires to a total of 120 students. All students who filled out the questionnaire were students who had participated in online learning and practicums on campus. and also conducting in-depth interviews on students to find out their opinions regarding social media to support their learning process. The collected data was analyzed using SPSS and analyzed using descriptive methods.